ADMINISTRATION: THE QUALITY OF PUBLIC SERVICE IN THE FIELD OF POPULATION - Soarubun, Johan (MAP Observer: Jurnal Penelitian Administrasi Publik, 2025)
Sukolilo District, Surabaya City as a government agency that provides public services at the sub-district level. As a regional apparatus for the City of Surabaya, Sukolilo District is an element of its territorial line whose activities are operational in nature, providing direct services to the community. As a public organization related to the implementation of service functions, the Sukolilo District Office, Surabaya City, as a public institution that provides licensing and non-licensing services, requires a level of service through improving the operational quality of employees, because high employee quality will reflect the quality of the organization as a whole. The aims of this study are as follows: To determine the quality of public services in the field of population administration (a case study of e-KTP services) in Sukolilo District, Surabaya City. The results of this study prove that the quality of public services is more dominant in providing a positive and significant influence on employee satisfaction. The conclusion obtained from this study is that the quality of public services in the field of population administration in e-KTP services in Sukolilo District, Surabaya City can be said to be good, this is because the facilities provided are adequate and the response from employees is good and the responsiveness of employees is very high. kind and empathetic from employees in solving problems in the field which aims to provide public service satisfaction to the community, but there are things that need to be improved, namely problems with the server network so that they affect service quality.